2016
DOI: 10.15406/jnmr.2016.03.00069
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters: Nanomedicine Potentials and Applications

Abstract: Attractive tiny gold nanoclusters (AuNCs) has opened golden gates of various applications in the world of technology. To name some of these applications we can refer to areas such as biosensor, contrast agent, drug and gene delivery system, etc. Here we will describe the potentials and applications of single and modified AuNCs for nanomedicine and theranostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When in this polarization state, microglia induce neuroinflammation by producing proinflammatory cytokines, nitric oxide (NO), and reactive oxygen species (ROS), which can lead to neural damage and impaired neurogenesis. , Moreover, M1 microglia can trigger astrocyte infiltration and activation (astrogliosis) . This can result in glial scar formation, which can form a barrier surrounding the injured region that prevents neuronal/axonal extension. , In contrast, M2 microglia are activated by interleukin 4 (IL-4) and IL-13, which induce neurogenesis and brain tissue regeneration by secreting anti-inflammatory neurotrophic factors such as IL-10, transforming growth factor-β (TGF-β), insulin-like growth factor 1 (IGF-1), basic fibroblast growth factor (bFGF), and brain-derived neurotrophic factor (BDNF). ,,, The shift from M2 microglia to M1 microglia has been associated with increased injury progression in stroke and TBI. , Hence, modulating microglial polarization from M1 toward M2 is considered as a potential therapeutic strategy for CNS regeneration and disease treatment. ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When in this polarization state, microglia induce neuroinflammation by producing proinflammatory cytokines, nitric oxide (NO), and reactive oxygen species (ROS), which can lead to neural damage and impaired neurogenesis. , Moreover, M1 microglia can trigger astrocyte infiltration and activation (astrogliosis) . This can result in glial scar formation, which can form a barrier surrounding the injured region that prevents neuronal/axonal extension. , In contrast, M2 microglia are activated by interleukin 4 (IL-4) and IL-13, which induce neurogenesis and brain tissue regeneration by secreting anti-inflammatory neurotrophic factors such as IL-10, transforming growth factor-β (TGF-β), insulin-like growth factor 1 (IGF-1), basic fibroblast growth factor (bFGF), and brain-derived neurotrophic factor (BDNF). ,,, The shift from M2 microglia to M1 microglia has been associated with increased injury progression in stroke and TBI. , Hence, modulating microglial polarization from M1 toward M2 is considered as a potential therapeutic strategy for CNS regeneration and disease treatment. ,, …”
mentioning
confidence: 99%
“…Recent advances in nanotechnology suggest that nanoparticles are promising drug delivery systems for the treatment of CNS disorders. , Gold nanoclusters (AuNCs) are an emerging class of fluorescent nanomaterial that show potential as biomedical imaging and biosensing agents due to their unique size and optical properties, excellent photostability, and biocompatibility. , Furthermore, due to their ultrasmall size (<3 nm), AuNCs can also readily cross biological membranes and can penetrate the blood–brain barrier (BBB) . As AuNCs have been reported to stimulate immune response, it is therefore necessary to examine whether this potential bioimaging tool would affect neuroinflammation or would the patient’s health be impaired during diagnosis.…”
mentioning
confidence: 99%
“…The polarization of macrophages (among the major cell types in the innate immune system) plays a key role in dental pulp infection and inflammation (Izumi et al, 1995;Iwasaki et al, 2011;Colombo et al, 2014). In our recent study (Xiao et al, 2020), we found that dihydrolipoic acidfunctionalized gold nanoclusters (DHLA-AuNCs) (Zhang et al, 2013;Li et al, 2014;Zhang and Wang, 2014;Shahsavari and Behroozi, 2016;Zhao et al, 2016;Zheng et al, 2017) efficiently regulated inflammatory responses. DHLA-AuNCs (referred to as AuNCs herein) directed the phenotype switch from M1 toward M2, creating an immune microenvironment beneficial for tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%